Mainland Women's Empowerment and Economic Policy Through Development Home Industry ( IRT) in Nagari Sungai Cubadak, Baso District, Agam Regency - Susanti, Lola; Irwan, Irwan; Yendra, Yendra (International Journal of Educational Research Excellence (IJERE), 2024)
Focus study in study This is analyze empowerment and policy economy Woman mainland through development Home Industry (IRT) in Nagari Sungai Cubadak , Baso District , Agam Regency . Theories used in research This is theory theory Adoption Innovation proposed by Rogers and Shoemaker (1971). Study This use approach qualitative with the data analysis process using thinking from Miles and Huberman. Data collection methods were carried out in several ways, namely participant observation, interviews and document study. This research focuses on mainland women through the development of Home Industries (IRT). The results of this research show that the form of empowerment carried out by the West Sumatra Province DP3AP2KB Service is providing awareness of the potential of nagari, carrying out technical guidance, forming women's groups through home industries and facilitating the development of home industry products produced. The form of policy carried out by the West Sumatra Province DP3AP2KB Service is planning-based policy, establishing management in developing mainland women's households and implementing mainland women's programs